2009
DOI: 10.1002/dmrr.1012
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Japan: a review of disease burden and approaches to treatment

Abstract: In recent years there has been rapid growth in diabetes in Japan which now is one of the nations most affected by the worldwide diabetes epidemic. Diabetes has been identified as a healthcare priority by the Ministry of Health, Labour and Welfare (MHLW). Type 1 diabetes is rare in Japan, and type 2 diabetes predominates in both adults and children. The growth in diabetes is due to increases in the number of people with type 2 diabetes associated with increased longevity and lifestyle changes. Approximately 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 51 publications
3
101
0
1
Order By: Relevance
“…The results showed that the incidence of cardiovascular disease decreases as more risk factor targets are achieved. (The targets are defi ned by the guidelines of the JAS, 14) Japan Society of Hypertension, 37) and Japan Diabetes Society 38) ). These results indicate that patients who achieve low LDL-C and concurrently have good blood pressure and glucose control, as well as good 0.690 *Achievement of risk factor targets was defi ned by using mean values during follow-up according to the following criteria: low-density lipoprotein cholesterol < 120 mg/dL, blood pressure < 130/80 mmHg, hemoglobin A1c (US National Glycohemoglobin Standardization Program) < 6.5%, and no smoking during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the incidence of cardiovascular disease decreases as more risk factor targets are achieved. (The targets are defi ned by the guidelines of the JAS, 14) Japan Society of Hypertension, 37) and Japan Diabetes Society 38) ). These results indicate that patients who achieve low LDL-C and concurrently have good blood pressure and glucose control, as well as good 0.690 *Achievement of risk factor targets was defi ned by using mean values during follow-up according to the following criteria: low-density lipoprotein cholesterol < 120 mg/dL, blood pressure < 130/80 mmHg, hemoglobin A1c (US National Glycohemoglobin Standardization Program) < 6.5%, and no smoking during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that morbid obesity is associated with insulin resistance and can increase the risk for developing diabetes mellitus type 2 (1,2). Consistent with these changes, the rates of pancreatic, colon, prostate and breast cancers, which are more frequent in Western nations, have increased in Japan (2-4).…”
Section: Introductionmentioning
confidence: 98%
“…Japan was ranked among the top 10 countries in a global survey of the numbers of people aged between 20 and 79 years with diabetes, and the prevalence of the disease in the Japanese population increased by more than 4% between 2000 and 2010 2,3 . Type 2 diabetes mellitus accounts for the majority of cases of diabetes in Japan 4 . Most patients with type 2 diabetes mellitus fail to attain and maintain glycemic targets with current therapies 5 .…”
Section: Introductionmentioning
confidence: 99%